Dengue vaccine development: status and future - Wilder-Smith, Annelies (Bundesgesundheitsblatt Gesundheitsforschung Gesundheitsschutz, 2019)
Dengue, the most common arbovirus, represents an increasingly significant cause of morbidity worldwide, including in travelers. After decades of research, the first dengue vaccine was licensed in 2015: CYD-TDV, a tetravalent live attenuated vaccine with a yellow fever vaccine backbone. Recent analyses have shown that vaccine performance is dependent on serostatus. In those who have had a previous dengue infection, i.e., who are seropositive, the efficacy is high and the vaccine is safe. However, in seronegative vaccinees, approximately 3 years after vaccination the vaccine increases the risk of developing severe dengue when the individual experiences a natural dengue infection. The World Health Organization recommends that this vaccine be administered only to seropositive individuals. Current efforts are underway to develop rapid diagnostic tests to facilitate prevaccination screening. Two second-generation dengue vaccine candidates, both also live attenuated recombinant vaccines in late-stage development, may not present the same limitations because of differences in the backbone used, but results of phase 3 trials need to be available before firm conclusions can be drawn. Dengue is increasingly frequent in travelers, but the only licensed dengue vaccine to date can be used only in seropositive individuals. However, the vast majority of travelers are seronegative. Furthermore, the primary series of three doses given 6 months apart renders this vaccine difficult in the travel medicine context.